Konstruksi Realitas Gubernur Jawa Barat Ridwan Kamil dalam Pemberitaan Relawan Uji Coba Vaksin Covid-19 - Dhea Risky Utami; M.E Fuady (UNISBA Press, 2022)
Abstract. This research entitled “The Construction of Reality of The Governor of West Java, Ridwam Kamil in The News of The Covid-19 Vaccine Trial Volunteers”. This research aims to determine the framing of online mass media coverage of TribunJabar.id and MindRakyat.com with the analysis model of Robert N. Entman. This research uses a qualitative method with a framing analysis study approach, focusing on online mass media texts. Data collection uses documents, literature studies, the internet, and interviews that are adapted to the current conditions and situation of the COVID-19 pandemic. The data collected was analyzed according to the data and the validity of the data was tested by the researcher. The results of the research obtained in the framing element that was carried out were related to how the media gave meaning in a news story. Ridwan Kamil became a volunteer for the Covid-19 vaccine trial. how reality is constructed in the social sphere through mass media which has a big role to influence the reader's subjective reality about Ridwan Kamil as a leader. Abstak. Penelitian ini berjudul “Konstruksi Realitas Gubernur Jawa Barat Ridwan Kamil Dalam Pemberitaan Vaksin Covid-19”. Penelitian ini bertujuan untuk mengetahui framing pemberitaan media massa online TribunJabar.id dan MindRakyat.com dengan model analisis Robert N. Entman. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi analisis framing, dengan fokus pada teks media massa online. Pengumpulan data menggunakan dokumen, studi pustaka, internet, dan wawancara yang disesuaikan dengan kondisi dan situasi pandemi COVID-19 saat ini. Data yang terkumpul dianalisis menurut data dan keabsahan data diuji oleh peneliti. Hasil penelitian yang didapat pada elemen framing yang dilakukan berkaitan dengan bagaimana media memberi makna dalam sebuah berita. Ridwan Kamil menjadi relawan uji coba vaksin Covid-19. bagaimana realitas dikonstruksi dalam ranah sosial melalui media massa yang berperan besar mempengaruhi realitas subjektif pembaca tentang Ridwan Kamil sebagai seorang pemimpin.